GoCrystal: A gamified visual analytics tool for analysis and visualization of atomic configurations and thermodynamic energy models. (October 2020) - Chung, Haeyong; Nandhakumar, Santhosh; Vasu, Gopinath Polasani; Vickers, Austin; Lee, Eunseok
In this article, we present GoCrystal, a new visual analytics tool for analysis and visualization of atomic configurations and thermodynamic energy models. GoCrystal's primary objective is to support the visual analytics tasks for finding and understanding favorable atomic patterns in a lattice using gamification. We believe the performance of visual analytics tasks can be improved by employing gamification features. Careful research was conducted in an effort to determine which gamification features would be more applicable for analyzing and exploring atomic configurations and their associated thermodynamic free energy. In addition, we conducted a user study to determine the effectiveness of GoCrystal and its gamification features in achieving this goal, comparing with a conventional visual analytics model without gamification as a control group. Finally, we report the results of the user study and demonstrate the impact that gamification features have on the performance and time necessary to understand atomic configurations.